Oral melatonin improves the detection of parasitemia in malaria - Chandan Kumar Kedarisetty; B Laksminarayana Samaga; Sudha Vidyasagar; Jayanthi Venkataraman (Journal of Infection in Developing Countries)
Introduction: Malaria is a growing global threat and a major cause of mortality in the tropics. The gold standard diagnosis is peripheral blood smear examination. It has been demonstrated that melatonin acts as messenger molecule in malaria pathophysiology. This concept was used to evolve a clinical study wherein use of exogenous melatonin could improve the chance of detection of the parasite.